Impact of the MSME Sector on Increasing Exports - Aiden Nightfall; Yasmin Zara (International Journal of Social Science and Humanity, 2024)
This research aims to analyze the impact of the Micro, Small and Medium Enterprises sector on increasing a country's exports. MSMEs have a significant role in the economy, especially in the context of globalization and international trade. This research method involves analysis of macro and micro economic data, including trade statistics and information related to MSMEs. The research results show that the MSME sector has a significant contribution to increasing exports, both through increasing the number of export units and product diversification. These findings provide important insights for policy makers, business people and researchers in understanding the strategic role of MSMEs in driving a country's export growth.